Fiscal Decentralization andEducationalOutcomes: Empirical Evidence from Pakistan (Journal of Asian Development Studies, 2024)
A large number of countries are transferring financial, administrative, and political powers to the local governments. In Pakistan, devolution reforms were launched through the Local Government Ordinance in 2001. This research investigates whether the higher autonomy of district governments could improve education outcomes in their respective districts or not. The Generalized Methods of Moments is employed for a panel of 34 districts of Punjab province, Pakistan, during 2003-2015.The results reveal that fiscal decentralization improves education outcomes in Punjab province of Pakistan. The enrolment in primary school is a measure of education outcome and improved in the districts of Punjab. In addition, the decentralization process during Pervez Musharraf's regime could not change the structure of the economy as a whole. Therefore, decentralization of the education sector in all provinces is suggested to reinforce the benefits of fiscal decentralization.